METHODS OF SOLVING HARD LOGIC PROBLEMS RELATED TO NEWTON'S PROBLEM - Iskakova , М.; Abulihayier, Н. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The main goal of all teachers in the secondary school algebra course is to improve student's logical thinking skills and develop creativity. Solving hard logic problems helps students systematically group problems by finding logical connections between them, and cultivate the ability to carefully read and analyze the conditions of logic questions, which will help students develop the habit of logical thinking. The logic questions in this scientific research are based on Newton's problems and compiled according to the national characteristics of our country. The level of compiled according questions corresponding to the 9th grade of city and republic Olympic questions in the secondary school algebra course. Students will learn to be able to use formulas, tables, and proportions to solve ticket office problems, cistern problems, and water pump problems related to Newton's problem. Thereby improving student's interest in solving hard logic problems and helping them confidently find solutions to hard problems encountered in the Mathematical Olympiad. Because these problems have national characteristics, so can increase student's interest in learning and love for the nation and country.